Pengabdian Kepada Masyarakat Melalui Pengembangan Batik Semoi Nusantara dengan Digital Marketing di Desa Argo Mulyo - Marsius Ferdnian; Muhammad Rizky Ferdiansyah; Rizal Arief Hidayat; Muhammad Faiz; Nurul Atika; Nurul Fahrisa Rahmadiani Irawan; Olivia Krisjayanti; Patrikson Goerge Bot; Praselia Amanda Putri; Vivian New Natalie Tampubolon; Yusia Helly Katartiza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
Community service through Real Work Lecture (KKN) activities is one form of the author's contribution to the community in overcoming existing problems by applying his theory into a service activity. This dedication was carried out by the author with the aim of providing an understanding of the importance of implementing Digital Marketing in a business activity through mentoring and socialization methods for Batik Semoi Nusantara business activities in Argo Mulyo Village, Sepaku District, North Penajam Paser Regency. In this service activity, the author did it in several stages, starting with discussions with the actors of Batik Semoi Nusantara business activities followed by execution and revision of activities and ending with the results of the author's service activities. What the author does in this devotion is, among others; logo creation, Maps point creation, Instagram account creation, and web contact person. The application of digital marketing does have a significant influence on business actors, even so there are still many who do not understand the true concept of digitalization, therefore, it is necessary to provide assistance to these business actors as well as what the author did on Batik Semoi Nusantara. There was a positive impact and response given after Batik Semoi Nusantara was given assistance regarding digitalization, one of which was increasing sales value and complete information for potential customers.